Genotypic diversity of anogenital human papillomavirus in women attending cervical cancer screening in Harare, Zimbabwe. Issue 9 (15th June 2017) - Dube Mandishora, Racheal S.; Christiansen, Irene K.; Chin'ombe, Nyasha; Duri, Kerina; Ngara, Bernard; Rounge, Trine B.; Meisal, Roger; Ambur, Ole H.; Palefsky, Joel M.; Stray‐Pedersen, Babill; Chirenje, Zvavahera M.
Abstract : Although anogenital cancers have been on a gradual rise in developing countries in the past few decades, they have been understudied. The objective was to investigate genotypic diversity of anogenital HPV amongst women reporting for routine cervical cancer screening in Harare in Zimbabwe. A cross‐sectional study that enrolled 144 women ≥18 years from a cervical cancer‐screening clinic was performed. Each woman provided a self‐collected cervico‐vaginal swab (VS) and a clinician‐collected anal swab (CCAS). HIV testing was offered and cervical cytology was performed. Both VS and CCAS samples were HPV genotyped, using amplicon sequencing of the L1 gene region with Illumina technology. Mean age of the women was 39.9 (range 18‐83 years, SD ± 11.0). HPV prevalence was 72% (104/144) in VS and 48% (69/144) in CCAS. The most common genotypes detected in both VS and CCAS were HPV18, HPV52, and HPV16. Sixty two percent of the subjects had multiple genotypic HPV infections. The odds of being HPV‐positive among HIV‐infected women were higher than in HIV‐negative women in both the vagina and the anus (CCAS OR = 4.8; CI 2.4‐9.8, P  < 0.001) and (VS OR = 2.9; CI 1.3‐6.4, P  = 0.005). High HPV prevalence and diverse genotypes were detected in both the vagina and anus. Anal oncogenic HPV infection was common. HPV 52 was one of the most common oncogenic genotypes in both the vagina and anus. HIV co‐infection played a significant role in the prevalence of HPV. These data have implications for design of primary and secondary programs for prevention of anogenital cancer in Zimbabwe.